Twórczość Jakuba Suszy. Kartka z dziejów literatury unickiej w Rzeczypospolitej XVII wieku - Pawlak, Wiesław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article presents the writings of Jakub Susza (c. 1610–1687), the Uniate Bishop of Chełm in 1652–1687. His most important works: the Latin biographies of Josaphat Kuntsevych ("Cursus vitae et certamen martyrii b. Iosaphat Kuncevicii...", Rome 1665) and Meletius Smotrytsky ("Saulus et Paulus Ruthenae Unionis sanguine beati Iosaphat transformatus sive Meletius Smotriscius...", Rome 1666) and a history of the revered icon of Our Lady of Chełm ("Phoenix redivivus albo obraz starożytny chełmski Panny i Matki Przenajświętszej", Zamość 1646, Lvov 1653, Zamość 1694), all represent little known literature written within the Uniate Church. Jakub Susza’s intellectual development, his education in Jesuit colleges in Braniewo, Pułtusk and Olomouc, and the characteristics of his work (consistent use of Polish and Latin as literary languages, the use of western Latin and Polish literary models) contribute to his image as an example of latinization and occidentalization (which then meant polonization) of higher Uniate clergy in the Commonwealth, though as a bishop he took care to preserve the religious identity of the Eastern church.
The Writings of Jakub Susza. A Page from the History of Uniate Literature in the Polish-Lithuanian Commonwealth in the 17th Century
Keywords: unia brzeska; Jakub Susza; literatura polska XVII w.; Union of Brest; Polish literature of the 17th century